STRATEGI INDONESIA MENGHADAPI STRUCTURAL POWER DALAM PERDAGANGAN KOPI SPESIALTI DI PASAR INTERNASIONAL - , HANUM SALSABILA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economic globalization resulted in a growing number of countries in the world are involved directly in international trade activities. Indonesia as one of the largest commodity-producing countries in the world have an important role in the global trading activities, including specialty coffee trade. Indonesian specialty coffee trade has a colonial history in which consumer countries have higher bargaining power. This phenomenon has become a misnomer because Indonesia as a country producers have not been able to become the market leader in the specialty coffee trade because until now the market leader is the countries that are not manufacturers of specialty coffee. This is due to the structural power that causes the Indonesian specialty coffee cannot be the center of the coffee world. Modernization and development of information technology makes Indonesia tries against stagnation in the development of the specialty coffee trade. With a strategy focused into (inward looking strategy) through the analysis of the value chain